In silico and in vivo wound healing studies of ursolic acid isolated from Clematis gouriana against GSK-3 beta - H. RAJA NAIKA; S. BHAVANA; JAIME A. TEIXEIRA DA SILVA; K. LINGARAJU; VIVEK CHANDRA MOHAN; V. KRISHNA (Smujo International, 2016)
Abstract. Naika HR, Bhavana S, Teixeira da Silva JA, Lingaraju K, Mohan VC, Krishna V. 2016. In silico and in vivo wound healing studies of ursolic acid isolated from Clematis gouriana against GSK-3 beta. Nusantara Bioscience 8: 232-244. Clematis gouriana Roxb. (Ranunculaceae) is an endemic medicinal plant of Western Ghats. Ursolic acid (UA) was isolated from the methanolic extract (ME), which was characterized by spectral studies, and was subjected to in silico studies on Glycogen synthase kinase 3-? (GSK3-?) protein, to inhibit protein function. UA showed least binding energy (-13.457 ?G) towards the binding site and molecular dynamics studies showed minimum potential energy and greater stability with target protein. Thus, UA may be considered as a potential inhibitor of the GSK3-? protein. The wound-healing activity was assessed by excision, incision, and dead space wound models on Wistar strain rats. The results of excision, incision, and dead space wound models showed significant activity. There was a significant increase in skin-breaking strength in rats treated with UA (562.36 ± 7.60 g). The effects of ME and UA on the dead space wound model were pronounced, with a significant increase in the weight of granulation tissue (26.33 ± 0.25 mg), tensile strength (647.00 ± 0.71 g), and hydroxyproline content (1793.83 ± 0.64 µg/100 g). Thus, UA-treated animals showed excellent wound-healing activity. Animals treated with nitrofurazone, ME and UA showed increased collagenation and decreased accumulation of macrophages at the site of injury.